ASPEK HUKUM KESEHATAN MENTAL DALAM SISTEM PERADILAN PIDANA: LITERATURE REVIEW TENTANG HAK TERSANGKA DAN TERPIDANA DENGAN GANGGUAN JIWA - Gunawan Widjaja (CV. Adiba Aisha Amira, 2026)
This article discusses the legal aspects of mental health within the criminal justice system, focusing on the rights of suspects and convicted persons with mental disorders. This study is motivated by the importance of legal protection for individuals with mental disorders who are involved in criminal proceedings, whether at the investigation stage, during trial, or whilst serving a prison sentence. This research employs a literature review method, examining various scientific sources, legislation and relevant policy documents. The findings indicate that suspects with mental disorders are entitled to a mental health assessment, legal aid, humane treatment, and legal proceedings that take their psychological capacity into account. Meanwhile, convicted persons with mental disorders are entitled to mental health services, appropriate care, suitable rehabilitation, and protection from discrimination within correctional institutions. However, the implementation of these protections still faces various obstacles, such as a lack of facilities, specialist staff, and inter-agency coordination. Therefore, a more humane and human rights-based legal approach is required so that the criminal justice system can provide fair protection for this vulnerable group.